The natural product argentatin C attenuates postoperative pain via inhibition of voltage‐gated sodium and T‐type voltage‐gated calcium channels. (15th January 2023) - Duran, Paz; Loya‐López, Santiago; Ran, Dongzhi; Tang, Cheng; Calderon‐Rivera, Aida; Gomez, Kimberly; Stratton, Harrison J.; Huang, Sun; Xu, Ya‐ming; Wijeratne, E. M. Kithsiri; Perez‐Miller, Samantha; Shan, Zhiming; et al.
Abstract: Background and Purpose: Postoperative pain occurs in as many as 70% of surgeries performed worldwide. Postoperative pain management still relies on opioids despite their negative consequences, resulting in a public health crisis. Therefore, it is important to develop alternative therapies to treat chronic pain. Natural products derived from medicinal plants are potential sources of novel biologically active compounds for development of safe analgesics. In this study, we screened a library of natural products to identify small molecules that target the activity of voltage‐gated sodium and calcium channels that have important roles in nociceptive sensory processing. Experimental Approach: Fractions derived from the Native American medicinal plant, Parthenium incanum, were assessed using depolarization‐evoked calcium influx in rat dorsal root ganglion (DRG) neurons. Further separation of these fractions yielded a cycloartane‐type triterpene identified as argentatin C, which was additionally evaluated using whole‐cell voltage and current‐clamp electrophysiology, and behavioural analysis in a mouse model of postsurgical pain. Key Results: Argentatin C blocked the activity of both voltage‐gated sodium and low‐voltage‐activated (LVA) calcium channels in calcium imaging assays. Docking analysis predicted that argentatin C may bind to NaV 1.7–1.9 and CaV 3.1–3.3 channels. Furthermore, argentatin C decreased Na + and T‐type Ca 2+ currents as well as excitability in rat and macaque DRG neurons, and reversed mechanical allodynia in a mouse model of postsurgical pain. Conclusion and Implications: These results suggest that the dual effect of argentatin C on voltage‐gated sodium and calcium channels supports its potential as a novel treatment for painful conditions.